2021
DOI: 10.1600/036364421x16128061189378
|View full text |Cite
|
Sign up to set email alerts
|

Urban Forest Fragments as a Living Laboratory for Teaching Botany: An Example from Federal University of Rio Grande do Norte, Brazil

Abstract: Abstract—“Plant blindness” is affecting humans’ relationships with plants, which has negative consequences for both science and conservation. It is, therefore, important to find new ways to promote societal interest in botany and plants. One possibility is encouraging the use of informal settings to promote curiosity and provide education to students. Forest fragments can be regarded as open air labs for teaching botany, especially on university campuses. We aimed to formally document the angiosperm diversity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Previous research shows much of the plant knowledge participants have comes from their parents (Bruschi et al., 2019; Gatt et al., 2007; Pilgrim et al., 2007) or informal educational experiences (Colli‐Silva et al., 2019; Corrêa et al., 2020; Lindemann‐Matthies, 2006), but that knowledge does not have to come solely from these sources. Other research has shown that through hands‐on activities with plants provided in the classroom, students can learn and create interest in plants (Dávila et al., 2021; de Oliveira Loureiro & Dal‐Farra, 2017; Hellinger et al., 2022; İri & Çil, 2020; Kissi & Dreesmann, 2018; Krosnick et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Previous research shows much of the plant knowledge participants have comes from their parents (Bruschi et al., 2019; Gatt et al., 2007; Pilgrim et al., 2007) or informal educational experiences (Colli‐Silva et al., 2019; Corrêa et al., 2020; Lindemann‐Matthies, 2006), but that knowledge does not have to come solely from these sources. Other research has shown that through hands‐on activities with plants provided in the classroom, students can learn and create interest in plants (Dávila et al., 2021; de Oliveira Loureiro & Dal‐Farra, 2017; Hellinger et al., 2022; İri & Çil, 2020; Kissi & Dreesmann, 2018; Krosnick et al., 2018).…”
Section: Resultsmentioning
confidence: 99%